Evaluasi Pertumbuhan dan Produktivitas Tiga Calon Kultivar Hibrida Jagung Manis (Zea mays L. Var. Saccharata) - Hafinda Niantama; Erlina Ambarwati, S.P., M.P.; Rani Agustina Wulandari (Vegetalika, 2025)
Plant characteristics are typically qualitative and quantitative traits that can be used as a standard for comparing other plants. The purpose of this study is to evaluate the growth and yield performance of three sweet corn promising hybrid cultivars and determine which sweet corn promising hybrid cultivars perform similarly to five commercial sweet corn hybrids as a control. The research was conducted at Karang Asam, Sendangtirto, Berbah, Sleman on November 2023–January 2024. The genotypes tested included three promising sweet corn hybrid cultivars, ANPF1 01, ANPF1 02, and ANPF1 03, as well as five commercial sweet corn hybrids used as control cultivars: Talenta, Jambore, So Sweet, Royal 76, and RS 8. The genotypes were distributed in a randomized complete block design with four replications. The data were analyzed using analysis of variance (ANOVA). If there were any significant differences, Tukey's HSD test was used at a 95% confidence level. The results showed that the promising hybrid cultivars ANPF 01, ANPF 02, and ANPF 03 performed similarly in terms of growth, yield, and quality (sweetness) to the five control commercial hybrids. ANPF 01, ANPF 02, and ANPF 03 are potential hybrid cultivars that could increase the diversity of sweet corn hybrid cultivars.